Path Analysis on the Associations between Infertility, Stress, and Depression among Women in Surakarta, Central Java - Retiyansa, Yesi; Indarto, Dono; Murti, Bhisma (Journal of Maternal and Child Health, 2019)
Background: In patriarchal societies like Indonesia, infertility is culturally considered as a problem of women. Most of the burden of infertility is borne by women because of a rapid decline in fertility with age, societal pressure and stigma. Infertility can affect psychological disorders such as stress and depression. This study aimed to examine the associations between infertility, stress, and depression among women in Surakarta, Central Java.Subjects and Method: This was  an analytic observational study with a cross sectional design. It was conducted in Surakarta, Central Java, from September to October 2018. A sample of 200 women of reproductive age was selected by fixed exposure sampling. The dependent variable was depression. The independent variables were social support, coping strategy, self-efficacy, infertility, and stress. Data on infertility was obtained from medical record. The other data were collected by questionnaire. The data were analyzed by path analysis.Results: The likelihood of depression among women was directly increased by stress (b= 2.09; 95% CI= 1.31 to 2.87; p<0.001) but decreased by good coping strategy (b= -1.57; 95% CI = -2.34 to -0.80; p <0.001). It was indirectly affected by infertility, self-efficacy, and social support. Conclusions: Depression is directly increased by stress but decreased by good coping strategy. It is indirectly affected by infertility, self-efficacy, and social support.Keywords: depression, stress, infertility, path analysis, women of reproductive ageCorrespondence: Yesi Retiyansa. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami No. 36 A, Surakarta 57126, Central Java. Email:yesi.retiyansa@gmail.com. Mobile: +6281252634625.Journal of Maternal and Child Health (2019), 4(4): 260-266https://doi.org/10.26911/thejmch.2019.04.04.05